Faktor-Faktor Yang Mempengaruhi Kejadian Penyakit Kaki Gajah Di Kecamatan Sausapor Kabupaten Sorong - A.L. Rantetampang,Yacob Ruru, Alfred Sroyer (Berita Kedokteran Masyarakat (BKM), 2003)
Background: Lymphatic filariasis is still a major public health problem in Papua and especially in Distric Sausapor of Sorong Municipality. It has many manifestations and its impact varies depending on the epidemiological setting. Its impacts can reduce the ability of work and morbidity. Out of ten main diseases in Sorong Papua, lympathic filariasis is in the 7th position.Objective: This study is aimed at finding out the incidence of Lymphatic Filariasis disease and its risk factors in District Sausapor of Sorong Municipality. The population consists of 1072 people from 9 villages and 344 of them were taken as sample by simple random sampling method.The data were collected using questionnaire and interview as primary data, and secondary data were taken from public health. The data, then, analyze using descriptive statistics to show their relationships.Result and conclusion: It can be concluded from the result that filariasis incidence in Distric Sausapor of Sorong is still high enough (13.66%). In addition, living behavior, environmental condition and health service are all factors considered in this study affect the incidence. Keywords: Lymphatic Filariasis, living behavior, environmental condition and health service.